Purification and Optimization of Uricase Enzyme Produced by Pseudomonas aeruginosa - Amirthanathan, Anderson; Vijayakumar, S (Journal of Experimental Sciences, 2011)
The uricase (urate oxidase) enzyme was extracted from Pseudomonas aeruginosa and purified by ammonium sulphate precipitation. The molecular weight of purified uricase was determined by SDS-PAGE electrophoresis using marker proteins of known molecular weight. The optimum temperature, pH and the effect of various metal ions on uricase activity were evaluated. The results showed that 70% ammonium sulphate concentration proved high uricase activity by 40.0 U/ml than other concentration and cell free supernatant. The molecular weight of purified uricase enzyme was estimated to be 33 kDa by SDS-PAGE profile. The optimum temperature and pH was detected at 35Ã‚Â°C and 8.5 for maximum uricase activity. Metal ions such as Co2+, Mn2+, Mg2+, Fe2+, Zn2+ and Cu2+Ã‚Â were reduced the enzyme activity to 33.17%, 92.18%, 72.47%, 32.73%, 64.32% and 90.10%, whereas Ca2+ enhanced uricase activity to 126%.Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â